Audel questions and answers for electrician's examinations - Rosenberg, Paul (Wiley Pub., 2004)
Your study guide for successTo pass the state licensing exam, you need knowledge and confidence. This comprehensive review guide gives you plenty of both. It's packed with sample questions to help you focus your efforts, review material on all aspects of the 2002 National Electrical Code (NEC), the lowdown on business competency requirements, and tips for studying and test-taking that will help you conquer any anxiety.* Learn the definitions, specifications, and regulations of the 2002 NEC* Find answers to questions you can expect on license exams* Brush up on taxes, unempl.